First Observations of Gigantic Jets From Geostationary Orbit. Issue 7 (4th April 2019) - Boggs, Levi D.; Liu, Ningyu; Peterson, Michael; Lazarus, Steven; Splitt, Michael; Lucena, Frankie; Nag, Amitabh; Rassoul, Hamid K.
Abstract: Here we report the first observations of gigantic jets (GJs) by the Geostationary Lightning Mapper (GLM) on board the Geostationary Operational Environmental Satellite‐R series. Fourteen GJs produced by Tropical Storm Harvey on 19 August 2017 were observed by both GLM and a ground‐based low‐light‐level camera system. The majority of the GJs produced distinguishable signatures in the GLM data, which include long continuous emissions, large peak flash optical energies, and small lateral propagation distances in comparison with other flashes observed by GLM. For two GJs with the best ground‐based images, each have a single pixel that contains the largest optical energy throughout the duration of the GJ and also coincides with the azimuth of the GJ from the video images. The optical energy of the pixel increases as the GJ propagates upward, reaches its peak when the GJ connects to the ionosphere, and then fades away. Key Points: Gigantic jets produce distinguishable signatures observed by the Geostationary Lightning Mapper The signatures include long continuous emissions, large peak flash energies, and small lateral propagation distances All of the largest energies during a gigantic jet come from a single GLM pixel